Quality of Life of Nurses Working in a Tertiary Level Hospital - Koju, Ganga Keshari; Pandey, Apsara (Journal of Nepal Health Research Council, 2023)
Background: Quality of life refers to persons’ sense of well-being based on their satisfaction with the important areas of their life. Work related stresses causes various physical and mental health problems to the nurses which reduces their quality of life. The study aimed to find out the quality of life of the nurses. Methods: A descriptive cross sectional, study was conducted among 135 nurses working in different units of a Tertiary Hospital, Kathmandu. Non-probability purposive sampling technique was used. Self- administered WHO Quality of Life–BREF Version tool was used to collect the data. Pearson Correlation was used to find out the relationship between actual quality of life and perceived quality of life of participants at p-value ?0.05.Results: More than two third (71.1%) of the participants had good perceived quality of life (Mean±SD=3.7±0.63) and 65.2% were satisfied with their health (Mean±SD = 3.52±0.80). Similarly, nearly half of the participants (48.1%) had below average mean score of quality of life. Overall mean score of quality of life obtained by participants was 60.74±9.02. The obtained mean score was highest in social domain (66.17±10.86) and lowest in environmental domain (52.8±10.6). There was significant correlation between actual quality of life and perceived quality of life of participants.Conclusions: As nearly half of the participants had below average quality of life, concerned authorities should pay attention to improve nurse’s working environment and physical health to improve their quality of life.Keywords: Nurses; quality of life; tertiary hospital; WHOQOL- BREF.